Chaotic synchronisation and secure communication via sliding-mode and impulsive observers. (1st January 2013) - Hamiche, Hamid; Guermah, Saïd; Djennoune, Saïd; Kemih, Karim; Ghanes, Malek; Barbot, Jean-Pierre
This paper addresses the design of a secure data transmission based on the synchronisation of two chaotic systems, with the use of unknown-input observers. The approach proposed here enhances the security level against intruders thanks to an intricate encryption system. It is shown also that this approach provides more robustness with respect to channel noise. The main feature consists in separating the encryption and synchronisation operations by using two coupled continuous chaotic systems in the transmitter. Technically, the scheme is based on impulsive and sliding mode unknown-input observers. This offers the advantage of estimating the (master) states and of reconstructing the unknown inputs simultaneously. The performances of the proposed method are highlighted by simulation results.